The changing role of time and social reality (Journal of Philosophy Culture and Political Science, 2020)
Differently from Philosophy and Natural Science, time has always been an important component in Social Research as human cognition tells us that the world is constantly changing in one temporal direction guided by the arrow of time. However, social time does not stand on its own. It connects to what is happening in the natural world as well as human individual psychological time. Classical conceptions ofKant and Husserl help to address the problem from its very foundation. It may well be that irreversibility is an objective natural phenomenon not just a subjective impression of living creatures. We must adopt an interdisciplinary view on time. The acceleration of speed in communication may have less significance for our lives than is normally expected, i.e. in the case of taking legal decisions. The only change we are currently experiencing in the context of application of Information Communication Technology in many spheres of social life may just be that many things happen more quickly. However, there is no essential difference. Human cognition is not becoming just spatial and atemporal.Key words: arrow of time, irreversibility, legal decisions, objective time, social time, subjective time.